+0

# SOS

+1
101
4

int(x+4/x^2-5x+6)

Guest Jun 16, 2017
Sort:

#1
+4154
+2

$$\int(x+\frac4{x^2}-5x+6)\,dx \\~\\ =\int(\frac4{x^2}-4x+6)\,dx \\~\\ =\int \frac4{x^2}\,dx+\int-4x\,dx+\int6\,dx \\~\\ =4\int x^{-2}\,dx-4\int x\,dx+6\int 1\,dx$$       Combine like terms.

Applying the power rule gives us...

$$=4(\frac{x^{-1}}{-1})-4(\frac{x^2}{2})+6(x) +c\\~\\ =-4x^{-1}-2x^2+6x+c$$                 , where   c   is a constant.

hectictar  Jun 16, 2017
#2
+18366
+1

integral( (x+4) / (x^2-5x+6) ) dx

$$\begin{array}{rcl} && \int { \frac{x+4} {x^2-5x+6} \ dx} \quad & | \quad x^2-5x+6 = (x-3)(x-2) \\ &=& \int { \frac{x+4} {(x-3)(x-2)} \ dx} \\ \end{array}$$

Partial fraction decomposition:

$$\begin{array}{|lrcll|} \hline & \frac{x+4} {(x-3)(x-2)} &=& \frac{A}{x-3} + \frac{B}{x-2} \\ & x+4 &=& A\cdot (x-2) + B\cdot (x-3) \\ x = 2: & 2+4 &=& A\cdot (2-2) + B\cdot (2-3) \\ & 6 &=& 0 + B\cdot (-1) \\ & 6 &=& B\cdot (-1) \\ & \mathbf{B} &\mathbf{=}& \mathbf{-6} \\ \\ x = 3: & 3+4 &=& A\cdot (3-2) + B\cdot (3-3) \\ & 7 &=& A\cdot (1) + B\cdot (0) \\ & 7 &=& A\cdot (1) \\ & \mathbf{A} &\mathbf{=}& \mathbf{7} \\\\ & \mathbf{\frac{x+4} {(x-3)(x-2)}} &\mathbf{=}& \mathbf{\frac{7}{x-3} - \frac{6}{x-2}} \\ \hline \end{array}$$

$$\begin{array}{rcl} && \mathbf{ \int { \frac{x+4} {x^2-5x+6} \ dx} } \\ &=& \int { \frac{x+4} {(x-3)(x-2)} \ dx} \\ &=& \int { \Big(\frac{7}{x-3} - \frac{6}{x-2} \Big) \ dx} \\ &=& 7\cdot \int { \frac{1}{x-3} \ dx} -6\int { \frac{1}{x-2} \ dx} \\ &\mathbf{=}& \mathbf{7\cdot \ln(|x-3|) -6\cdot \ln(|x-2|) +c }\\ \end{array}$$

heureka  Jun 16, 2017
edited by heureka  Jun 16, 2017
#3
0

Take the integral:
integral(4/x^2 - 4 x + 6) dx

Integrate the sum term by term and factor out constants:
= -4 integral x dx + 4 integral1/x^2 dx + 6 integral1 dx

The integral of x is x^2/2:
= -2 x^2 + 4 integral1/x^2 dx + 6 integral1 dx

The integral of 1/x^2 is -1/x:
= -4/x - 2 x^2 + 6 integral1 dx

The integral of 1 is x:
Answer: | = -2 x^2 + 6 x - 4/x + constant

Guest Jun 16, 2017
#4
0

Take the integral:
integral(x + 4)/(x^2 - 5 x + 6) dx
Rewrite the integrand (x + 4)/(x^2 - 5 x + 6) as (2 x - 5)/(2 (x^2 - 5 x + 6)) + 13/(2 (x^2 - 5 x + 6)):
= integral((2 x - 5)/(2 (x^2 - 5 x + 6)) + 13/(2 (x^2 - 5 x + 6))) dx
Integrate the sum term by term and factor out constants:
= 1/2 integral(2 x - 5)/(x^2 - 5 x + 6) dx + 13/2 integral1/(x^2 - 5 x + 6) dx
For the integrand (2 x - 5)/(x^2 - 5 x + 6), substitute u = x^2 - 5 x + 6 and du = (2 x - 5) dx:
= 1/2 integral1/u du + 13/2 integral1/(x^2 - 5 x + 6) dx
The integral of 1/u is log(u):
= (log(u))/2 + 13/2 integral1/(x^2 - 5 x + 6) dx
For the integrand 1/(x^2 - 5 x + 6), complete the square:
= (log(u))/2 + 13/2 integral1/((x - 5/2)^2 - 1/4) dx
For the integrand 1/((x - 5/2)^2 - 1/4), substitute s = x - 5/2 and ds = dx:
= (log(u))/2 + 13/2 integral1/(s^2 - 1/4) ds
Factor -1/4 from the denominator:
= (log(u))/2 + 13/2 integral4/(4 s^2 - 1) ds
Factor out constants:
= (log(u))/2 + 26 integral1/(4 s^2 - 1) ds
Factor -1 from the denominator:
= (log(u))/2 - 26 integral1/(1 - 4 s^2) ds
For the integrand 1/(1 - 4 s^2), substitute p = 2 s and dp = 2 ds:
= (log(u))/2 - 13 integral1/(1 - p^2) dp
The integral of 1/(1 - p^2) is tanh^(-1)(p):
= (log(u))/2 - 13 tanh^(-1)(p) + constant
Substitute back for p = 2 s:
= (log(u))/2 - 13 tanh^(-1)(2 s) + constant
Substitute back for s = x - 5/2:
= (log(u))/2 + 13 tanh^(-1)(5 - 2 x) + constant
Substitute back for u = x^2 - 5 x + 6:
= 1/2 log(x^2 - 5 x + 6) + 13 tanh^(-1)(5 - 2 x) + constant
Factor the answer a different way:
= 1/2 (log(x^2 - 5 x + 6) + 26 tanh^(-1)(5 - 2 x)) + constant
Which is equivalent for restricted x values to:
Answer: | = 7 log(3 - x) - 6 log(2 - x) + constant

Guest Jun 16, 2017

### 4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details